(untitled) (Филолошке студије, 2020)
Since the plots of the novels Đuka Begović and Zemja (Land) by Elin Pelin are constructed around the ancient mythical murder motifs of patricide and fratricide, this analysis relies on mimetic theory by Rene Girard that is also constructed as a theoretical explanation of the afore mentioned mythical murders. Although Girard denies libidinal and object-directed causation of desire, in his polemics with the Freudian model of the libidinal desire Girard implies that there is a privileged object of desire in the patriarchal order – i.e. women because the father is the natural model for the son, and men’s desire for women is interindividually directed and intensified. Money and some other types of property are the privileged objects in a capitalist society – since the desires of all members of the society are concentrated around them. The crisis of patriarchal order in Đuka Begović causes the loss of degree and the elevation of the structural positions of the father and the son, which then becomes the motive for Đuka’s patricide. On the other hand, the idealization and the persevered authority of the older brother causes Enjo’s repentance and the semi-establishing of the patriarchal order in the novel Zemja. The idealized older brother in the Pelin’s novel preserves the function of the paternal authority, and the father in Kozarac’s novel loses his authority and degree so he functions as the rival brother within the framework of the Girardian mimetic theory.